Ion transport systems in kidney and urinary bladder of two Antarctic teleosts, Chionodraco hamatus and Trematomus bernacchii - MASINI, MARIA ANGELA; M. STURLA; P. PRATO; B. UVA (Polar Biology, 2001)
Na+-K+-ClA cotransport and Na+/K+AT- Pase were studied by immunohistochemistry in the kid- ney and urinary bladder of Trematomus bernacchii and Chionodraco hamatus. The activity was correlated to the density of mitochondria. The ®rst segment of the renal proximal tubule was more active than the second one. In T. bernacchii and the temperate marine teleost Pagellus bogaraveo, the immunoreactivity for the antibody to cotransporters and to the —-subunit of the sodium pump was stronger than in the ice®sh. This dierence indicates in the kidney of the ice®sh, a weaker secretory activity, a consequent lower osmolarity in the lumen and lower water loss, which correlates well with the need for a greater blood volume in the ice®sh. The epithelium of the urinary bladder in T. bernacchii, where intense im- munostaining was observed, was composed of columnar cells. In C. hamatus the columnar cells, where the im- munostaining was weaker, lined only a portion of the urinary bladder, the other region being composed of cuboidal cells.